Identifikasi faktor-faktor yang mempengaruhi daya saing dan posisi strategik KUB Batik Banyumasan - Intan Nawangsari Sutarto (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The popularity of batik in Indonesia was increasing nevertheless, however batik Banyumasan seemed difficult to penetrate the market.  Banyumas Batik is still less pamor compared to the batik of Pekalongan, Solo, and Yogyakarta, this is seen from low productivity and also the product has not been able to penetrate the export market. This research aims to identify factors that affect the competitiveness of KUB Batik Banyumasan as well as analyze and determine the strategic position of KUB Batik Banyumasan (Pringmas KUB case study). In identifying the factors influencing the competitiveness and strategic position used Diamond Porter model, value chain, VRIO, IFAS, EFAS and SFAS matrix. The respondent in this study were divided into expert respondent and the company's internal informant. Based on the results of the score calculation on the internal factor and the external factor of Banyumasan batik’s industry KUB Pringmas obtained in the quadrant I indicate the position of the company is highly profitable, the company has the opportunity and strength, so can take advantage of existing opportunities. The strategy that must be set for the company in this position is to support the growth oriented strategy.